349 Evaluation of a Fenugreek Extract Fed to Sows from 90 Days of Gestation through Lactation on Sow and Litter Performance. (10th April 2018) - Graham, A; Knopf, B; Sandberg, F B; Soltwedel, K T; Bible, M R; Greiner, L
Abstract: One hundred and sixty sows (PIC Camborough, PIC, Hendersonville, TN) were allocated by parity block (parity 1 vs parity 2+) to one of four dietary 0.00%, 0.05%, 0.15%, or 0.25% fenugreek (Nutrifen, Furst McNess, Johnston, IA) starting at d90 of gestation. All diets were formulated to meet or exceed NRC (2012). Sows were porcine reproductive respiratory syndrome and porcine epidemic diarrhea virus negative. Sows were weighed at d90 of gestation, upon entry into the farrowing rooms (235.2 ± 7.9 kg) and at weaning. Litter weights were collected at birth, 48 hours post-farrow and weaning (average d 20). Daily feed intake was recorded from entry to the farrowing room until weaning to observe effects of treatment on feed intake. Sow serum was collected from 9 sows per treatment at the initiation of the study, at farrowing and at weaning for glucose, IgG and RBC values. The weaning piglet serum (2 pigs per each of the 9 serum sampled sows) was tested for IgG content. Five mls of sow colostrum (day of farrowing) were analyzed for IgG content, protein, glucose, lactose, and fat. Data were analyzed as a randomized complete block using the PROC MIXED procedure of SAS. Orthogonal polynomial contrasts were used to determine the effect of inclusion levels of Fenugreek on sows. In addition, differences among treatments were considered significant with P -value ≤ 0.05, and a trend if P -value > 0.05 and ≤ 0.10. Feeding fenugreek resulted in a significant quadratic improvement in lactation feed intake (4.87, 5.22, 5.42, 5.06 kg, respectively; P < 0.01). Feeding fenugreek resulted in a linear reduction in sow lactation weight loss (-6.51, -5.74, -0.21, 1.68 kg, respectively; P < 0.01). There was a trend for a quadratic effect of fenugreek level on daily litter weight gain (2.45, 2.57, 2.64, 2.45 kg, respectively; P < 0.10). The effect of fenugreek on number of pigs weaned was not significantly different (10.84, 11.43, 11.35, 10.86, respectively; P = 0.12). In this trial, the feeding of 0.15% fenugreek resulted in a quadratic improvement in lactation feed intake and daily litter gain.